(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Static routing is one of the most fundamental routing techniques used in computer networks to manually define paths between source and destination networks. Unlike dynamic routing protocols, which automatically update routes using network topology changes, static routing provides network administrators with complete control over the routing table. This research paper presents a detailed study on the implementation, advantages, limitations, and performance of static routing in modern network environments. The study further evaluates the suitability of static routing in enterprise and small-scale networks, emphasizing security, reliability, and ease of configuration. Using Cisco routers and simulation tools, the paper demonstrates the configuration and behavior of static routes and highlights how manually configured paths can significantly enhance stability in predictable network environments.